Polyelectrolyte functionalized lamellar graphene oxide membranes on polypropylene support for organic solvent nanofiltration - Hua, Dan; Chung, Tai-Shung (Carbon (New York), 2017)
We have reported, for the first time, a straightforward and eco-friendly approach to molecularly design graphene oxide (GO) nanosheets on robust hydrophobic polypropylene (PP) supports with excellent adhesion and superior separation performance for organic solvent nanofiltration (OSN) of dye/ethanol mixtures. The approach consists of (1) grafting the PP surface with polyethylene glycol (PEG) with the aid of argon plasma (TPP), (2) a pressure-assisted filtration of GO dispersion and (3) functionalization by various polyelectrolytes. We find that the TPP/GO membrane modified by hyperbranched polyethylenimine (HPEI) on its outmost layer has high rejections toward cationic dyes. It has a rejection of 95% toward Alcian blue with a high permeance of 14.9 L m−2 h−1 bar−1. Similarly, it exhibits excellent anionic dye/ethanol separation if it is modified by poly(styrenesulfonate) (PSS) on its outmost layer. It shows a rejection up to 97% toward Rose bengal with a total permeance of 3.1 L m−2 h−1 bar−1. Experimental results confirm that both molecular sieving and electrostatic repulsion play critical factors for GO based membranes to separate dye/organic solvent mixtures. This work may not only widen the selection of membrane support materials for GO deposition but also provide useful insights for developing GO based membranes for OSN. [Display omitted]